2012
DOI: 10.1136/bmjopen-2012-000841
|View full text |Cite
|
Sign up to set email alerts
|

A new user cohort study comparing the safety of long-acting inhaled bronchodilators in COPD

Abstract: ObjectiveTo investigate a possible increased risk observed in tiotropium clinical trials of stroke and other adverse events.DesignNew users of long-acting anticholinergic therapy (tiotropium HandiHaler®) were compared with new users of long-acting β-agonist (LABA) monotherapy, and propensity scores were used to control confounding.SettingUK healthcare system general practitioner electronic medical record database.Participants10 840 patients newly prescribed tiotropium (n=4767) or LABA (n=6073), at least 40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 36 publications
4
31
0
1
Order By: Relevance
“…Ezekre az ipratropiumnál leírtak érvényesek. Jara viszont nemcsak a meglévő szívbetegségeket, szívgyógyszereket közli, hanem a dohányzást és a spirográfi át is, sőt a vesefunkciót is fi gyelembe vette [10]. Anyagában a tiotropium mellett az angina és a szívinfarktus szaporodott, az összmortali-tás csökkent, az arrhythmia és a szívelégtelenség válto-zatlan maradt.…”
Section: Tiotropium Handihalerunclassified
“…Ezekre az ipratropiumnál leírtak érvényesek. Jara viszont nemcsak a meglévő szívbetegségeket, szívgyógyszereket közli, hanem a dohányzást és a spirográfi át is, sőt a vesefunkciót is fi gyelembe vette [10]. Anyagában a tiotropium mellett az angina és a szívinfarktus szaporodott, az összmortali-tás csökkent, az arrhythmia és a szívelégtelenség válto-zatlan maradt.…”
Section: Tiotropium Handihalerunclassified
“…A recent study investigated the medical records database of general practitioners in the UK in terms of new users of long-acting anticholinergic therapy (tiotropium HandiHaler ® , Boehringer Ingelheim Pharmaceuticals, Inc, Ridgefield, CT, USA) (n = 4767) in comparison with new users of LABA monotherapy (n = 6073) 39. They found that more cardiovascular events occurred when using tiotropium compared with LABA for stroke (HR, 1.49; 95% CI 0.91–2.15), myocardial infarction (HR, 1.38, 95% CI 0.88–2.15), and angina (HR 1.26; 95% CI 0.72–2.21) compared with LABA.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Furthermore, to standardize the reporting of primary CV events (MI, stroke, or heart failure) between centers (which may adopt different interpretations and event definitions), only events confirmed by the blinded adjudication committee are included. The expected event rates for MI, stroke, and heart failure are 98, 108, and 168,60 although as the study is event-driven, recruitment rates will be adjusted once the actual event rate in this population is known.…”
Section: Introductionmentioning
confidence: 99%